Local INR calibration of the Owren type prothrombin assay greatly improves the intra- and interlaboratory variation - Hillarp, Andreas; Egberg, Nils; Nordin, Gunnar; Stigendal, Lennart; Fagerberg, Inger; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2004)
In 1999, a simplified procedure for calibration of the Owren prothrombin time (Owren PT) assay was introduced by a working group of the organisation for national quality assurance in laboratory medicine in Sweden. The new protocol allowed local calibration by means of only two lyophilised national plasma calibrators and expression of results as an international normalized ratio (INR). This is our report of a three-year follow-up involving the analysis of data from all laboratories, in hospitals (n=88 in 2002) and primary health care units (n=246 in 2002) that perform the Owren PT assay in Sweden. The interlaboratory variation was significantly improved after the introduction of the new calibration procedure. For the larger hospital-based laboratories, the mean coefficient of variation (CV) was reduced from 7.9% to 5.2% (p<0.0001) when analysing test materials with INR range 2-4. In the higher INR range (>4), the CV was reduced even further, from 10.4% to 6.8% (p<0.0001). The corresponding results from smaller laboratories in the primary health care units showed a similar decrease in CV from 8.2% to 5.7% in the INR range 2-4 (p<0.0001). At the INR range >4, the CV was reduced from 9.5% to 7.8%. The intralaboratory variation was also improved for both types of laboratory categories. This study shows an improved precision, with CV less than 6% at the therapeutic INR range, for both hospital-based laboratories and smaller laboratories in the primary health care system. The results indicate that the Owren PT assay is well suited for local INR calibration employing only two calibrant plasmas in a simplified procedure.
Keywords: Prothrombin time; international normalized ratio; standardization; lyophilized plasmas; external quality assessment